Proton-Ligand and Metal-Ligand Stability Constant of Newly Synthesiezed Bis-Chalcones and Their Bromo Derivatives - Kinhikar, R.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
The interaction of Cu(Il) and Th(IV) with 1,1-bis-[2-hydroxy-3- (3-aryl-prop-2-en-1-one)-5-methyl phenyl] methanes and their bromo derivatives has been investigated by Bjerrum method as adopted by Calvin and Wilson. The stability constants of complexes containing 1 : 1 and 1 : 2 ratio of Cu(II) and Th(IV) to ligand have been estimated at (27 ± 0.1 oC) and 0.1 M ionic strength (NaCIO4) in 80% DMF-water mixture.